Drawing and Play as Windows into a Child’s Multimodal Meaning-Making Development during COVID-19 - Brass, Laura; Jenson, Jennifer (Language and Literacy / Langue et littératie, 2023)
Framed within multimodality and situated in a bounded socio-geographical context (i.e., Vancouver), this ethnographic case study provides an in-depth analysis of a bilingual 8-year-old girl’s literacy practices of meaning-making established across varied semiotic modes (i.e., linguistic, visual, audio, spatial, embodied, kinesthetic) during COVID-19. The study draws upon 13 open-ended informal interviews, three sessions of imaginative play, and 16 participant-generated artifacts. The findings revealed two themes (i.e., drawing as collective meaning-making; play as embodied, anthropomorphic meaning-making) that show how the child’s interactions with humans and nonhumans (e.g., toys, objects) contributed to her multimodal meaning-making during the pandemic, which might be beneficial for children in different contexts.